Ответы и объяснения

2013-08-25T15:45:02+04:00
Х + 4 = z                                                                              x + 4 = y + 3
y + 3 = z    => (Подставим значение z в первое уравнение) y + 3 =z          =>
6x - 5y = 2                                                                          6x - 5y = 2 

x = y - 1             x = y - 1          x = y - 1            x = 7
y + 3 = z      =>  y + 3 = z    => z = y + 3      => z = 11 
6x - 5y = 2          6y - 5y = 8       y= 8                 y = 8